Prototype Desain Keamanan Login Menggunakan Biometrik Wajah Dengan Metode Eigenface - sugeng widodo (LPPM Universitas Mercu Buana Yogyakarta, 2020)
Login security is a major problem when using a device that is connected in an outside network or internet network. Therefore a data security using face biometrics is performed. Eigenface is a face recognition method based on the Principal Component Analysis (PCA) algorithm. In short the process is that the image is represented in a combined vector which is made into a single matrix. From this single matrix, we will extract a main feature that will distinguish between one face image and another face image. In using the biometric login system this face is the user registering to the system then the user's face will be trained so that the user will be recognized by the system for login purposes. When a user logs in, the user's face data will be processed in real time and matched with the data in the database so that if the data match, the user will successfully log in. The standard face distance from the webcam is 50-60 cm, while the minimum exposure level of the face that can be recognized is 5 lux, and the angle of the face that the system can still recognize is 40 °.